A RETROSPECTIVE STUDY OF OCCURRENCES OF VIOLENCE AGAINST WOMEN RECORDED IN A SPECIALISED POLICE UNIT - Maria Lúcia Raimondo; Liliana Maria Labronici; Liliana Müller Larocca (Universidade Federal do Paraná, 2013)
This quantitative, descriptive and retrospective research aimed to outline the profile of violence perpetrated against women in a municipality in the state of Paraná. The data was obtained from 4,478 Police Reports and Minor Incidents recorded in the Women's Protection Police Unit, between 2005 and 2009. Analysis was undertaken through descriptive statistics. The results evidenced that 93.4% of the victims reside in the urban area; that 82.8% were aged between 20 and 59 years old; that 54.2% live in a stable relationship; that 69.4% had finished basic education; and that 52.7% carried out paid work. 70.1% of the incidents of violence took place within the home, and the most frequent forms were psychological and physical. The main aggressors were family members, especially spouses; 20.9% of the aggressors used alcohol or drugs. Violence is a problem present in the daily life of the women in the municipality, and outlining its profile is shown to be an important tool for planning policies and actions, with a view to its eradication.